2019
DOI: 10.1002/jcb.28822
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA circ_0103552 forecasts dismal prognosis and promotes breast cancer cell proliferation and invasion by sponging miR‐1236

Abstract: Breast cancer (BC) is a fatal malignancy, which has a high incidence and mortality across the world. Circular RNAs (circRNAs) have crucial roles in tumor initiation and progression. In this project, a newly found circRNA, circ_0103552 was explored. Quantitative real‐time polymerase chain reaction was applied to measure its expression in the patients' tissue specimens and cells. In addition, Fisher's exact test, Kaplan‐Meier curves and Cox regression model were conducted to discover the clinical significance of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(21 citation statements)
references
References 32 publications
2
19
0
Order By: Relevance
“…Prior studies have revealed that circRNAs could serve as sponges of miRNAs [27][28][29]. To figure out whether circDENND4C regulates breast cancer progression by sponging miRNAs, its targets were explored by bioinformatics analysis using starBase, predicting that miR-200b and miR-200c might be sponged by cir-cDENND4C, which was confirmed by luciferase activity and RIP assays.…”
Section: Discussionmentioning
confidence: 89%
“…Prior studies have revealed that circRNAs could serve as sponges of miRNAs [27][28][29]. To figure out whether circDENND4C regulates breast cancer progression by sponging miRNAs, its targets were explored by bioinformatics analysis using starBase, predicting that miR-200b and miR-200c might be sponged by cir-cDENND4C, which was confirmed by luciferase activity and RIP assays.…”
Section: Discussionmentioning
confidence: 89%
“…Numerous studies demonstrated that circRNA/miRNA axis played critical roles in the progression of cancers. For instance, circ0103552 significantly promoted cell proliferation and invasion via sponging miR-1236 in breast cancer (10). Mao et al (11) demonstrated that circ0068871 could accelerate the progression of bladder cancer by targeting miR-181a-5p and then regulate the expression of FGFR3 and activate STAT3.…”
Section: Introductionmentioning
confidence: 99%
“…Of all prognostic studies, one study investigated the prognostic value of tumor‐inhibitory circRNAs on DFS, 40 together with the other study assessed a combination of 10 circRNAs using The Cancer Genome Atlas clinical data for BC, 41 were both eliminated. Finally, 16 articles, 20‐35 including 4 individual studies on the diagnosis and 13 on the prognosis, were included for the subsequent meta‐analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Given that circRNAs are insensitive to nucleases and more stable than ordinary linear RNA, they are expected to be new biomarkers for monitoring various cancers 18,19 . And circRNAs are intensively reported to have the potential of the early diagnosis and prognostic prediction of BC as novel molecular biomarkers 20‐35 . However, the appraisals of their efficacy are commonly limited by the small sample size, high bias, and single‐center population of the already reported trials.…”
Section: Introductionmentioning
confidence: 99%